A Case in Relations between Great Powers and Small States - France's Recognition of Finnish Independence, 1917-1918 - Clerc Louis (De Gruyter Open Ltd, 2022)
Abstract
What are the most important variables explaining the 4 January 1918 decision by the French Government to recognise Finland’s independence? This short contribution to the Special Issue aims at giving a broad overview of developments explaining this decision. It will first of all introduce general notions concerning France’s relation with “nationalities” during the First World War. It will more specifically describe the geopolitical environment of the winter 1917–1918, when France looked for ways to react to the crumbling of its Russian ally against Germany. It will also emphasise the way domestic developments and the long-term action of Finnish national networks helped in shaping up this decision. Finally, based on this example, it will consider various ways for small states to try and influence their international environment.